Implementation of international standards in the sphere of higher education to national legislation of the Republic of Kazakhstan - Alibekova, A.; Rakisheva, A. (Право и государство, 2017)
The article considers the international standards adopted by United Nation Organization in the sphere of higher education. During the analysis of the international instruments the authors have made the conclusion that higher education is considered as the right of everyone to higher education from the aspect of its availability and accessibility. Besides, the right to education refers the development of human personality and dignity and involves theoretical and practical directivity. The authors have come to the conclusion that national legislation of the Republic of Kazakhstan conforms to international standards in the sphere of higher education but there are some contradictions within the national acts themselves.
Keywords: international law; right to higher education; higher education; availability; international standard; United Nations Organization; international treaty; implementation; legislation; Research Subject Categories::LAW/JURISPRUDENCE